Effect of room temperature and refrigerated storage on automated complete blood count: A longitudinal study - Anu Jaya; Naveen Kakkar; MJoseph John (Wolters Kluwer Medknow Publications, 2022)
Objective: Delay in complete blood count (CBC) analysis is likely in laboratories with very high workload or when the samples are collected off site for testing in centralized laboratories. This research was done to study the stability of blood cell parameters in automated CBC at the room temperature (20°C-24°C) storage after 24 h and refrigerated (2°C-8°C) storage after 24 and 48 h. Materials and Methods: Automated CBC was done initially on 500 randomly selected blood samples in a 3-part hematology analyzer. Of these, 250 samples were stored at the room temperature (20°C-24°C), and the rest were refrigerated at 2°C-8°C. Re-analysis after 24 h was done for both groups. Data were analyzed using the Pearson correlation coefficient, ANOVA, and repeated-measure ANOVA. Results: Refrigerated samples stored at 2°C-8°C showed good stability for all hematological parameters (P > 0.5), except for mean platelet volume (MPV) in comparison with those at the room temperature storage. MPV showed a statistically significant (P < 0.001) rise on refrigerated storage. In the room temperature storage group, hematocrit (Hct), mean corpuscular volume, mean corpuscular hemoglobin concentration, red cell distribution width, MPV, and granulocyte percentage showed significant difference compared to the initial values. In the extended 48 h refrigerated storage group, all CBC parameters except Hct showed acceptable stability. Conclusion: The storage of blood samples at the room temperature and on refrigeration (2°C-8°C) for 24 h has shown acceptable stability of most of the automated CBC parameters. Refrigeration retained the true values over the room temperature storage and should be recommended if a delay in testing is expected.